Analysis of Geomorphic Factors Related to Seismic Activity in Lai Chau Hydropower Reservoir in the Period 2015 - 2024 - Van Duan, Bui; Quoc Van, Dinh; Lizurek, Grzegorz; Nowaczyńsk, Izabela; Wiszniowski, Jan; Van Vung, Vi; Ba Manh, Le; Thuy Linh, Nguyen; Minh Tuan, Vu; Thanh Hai, Nguyen; Anh Duong, Nguyen (VNU Journal of Science: Earth and Environmental Sciences, 2025)
Following the reservoir impoundment, the seismic activity in the Lai Chau reservoir area and its vicinity has increased significantly. The changes in frequency of local earthquakes depends on: i) The type of rocks below the reservoir; ii) The slip tendency of faults in the reservoir area; iii) The Coulomb stress change on faults in the reservoir area; and iv) The history of the reservoir filling and spillage. The results show that the granite massif of the Phu Si Lung complex is located below the upstream area of ​​the reservoir at a depth of about 3,000-4,000 m; when water percolates down through this type of rocks, it will cause some fractures in the rock to become saturated with water, making stress in the rock reach the failure threshold. Under the impact of the modern regional tectonic stress field, the faults connected to the reservoir (F-1, F-2, F-3, F-4) tend to slip at moderate to high rates, and the Coulomb stress change is also clearly shown on these faults. These factors, together with the annual fluctuations in the reservoir water level between the rainy and dry seasons, have mutual influences, triggering the earthquakes to occur in the Lai Chau reservoir area and its vicinity in the period 6/2015 - 6/2024.